Methyl Blue Dye Adsorption Using Activated Eggshell: Kinetics, Isotherm, and Phytotoxicity Analysis - Hasan, Al Shariar; Dutta, Sagar Kumar; Bashar, Abul; Dhar, Palash Kumar; Haque, Rezaul (Sustainability & Circularity NOW, 2025)
Aesthetic and health concerns have been raised about removing color from wastewater. Industrial activity is a major source of water contamination. Dyes can be hazardous, carcinogenic, and mutagenic to wildlife, plants, and humans. Consequently, it is essential to process wastewater prior to its release into the environment. Fabrics, leather tanning, paper, plastics, and printing all employ synthetic dyes like methyl blue (MB). MB is one of the triphenylmethane acid dyes and anionic dyes. In this investigation, refuse eggshell powder was carbonized and subsequently activated with lemon juice extract as an activating agent. The activated carbon eggshell (ACE) that was prepared was subjected to Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), and zero point charge (ZPC). The adsorption rate was significantly influenced by several parameters, including pH, adsorbent dosage, initial concentration, contact time, and temperature. Additionally, isotherm models (including Langmuir, Freundlich, Temkin, and Dubinin–Radushkevich (D–R) isotherm models), kinetic models (including pseudo-first-order, pseudo-second-order, Elovich, intraparticle diffusion, and liquid-film diffusion models), and phytotoxicity studies were investigated. The optimum adsorption was achieved at a pH of 2, adsorbent dosage of 1.0 g, contact time of 70 min, and initial (MB) dye concentration of 40 mg/L. The maximal (MB) dye removal efficiency was initiated at 98.94%. This adsorbent (ACE) is expected to be well received as a more cost-effective alternative to other adsorbents.
Keywords: Eggshell; Adsorption; Methyl blue; Kinetics; Isotherm; Phytotoxicity